2011
DOI: 10.1002/jbm.a.33252
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a novel pluronic F127/graphene nanohybrid for pH responsive drug delivery

Abstract: Herein, a novel Pluronic F127/graphene nanosheet (PF127/GN) hybrid was prepared via an one-pot process including the simultaneous reduction of graphene oxide and assembly of PF127 and GN. The nanohybrid exhibits high water dispersibility and stability in physiological environment with the hydrophilic chains of PF127 extending to the solution while the hydrophobic segments anchoring at the surface of graphene via hydrophobic interaction. The PF127/GN nanohybrid is found to be capable of effectively encapsulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(74 citation statements)
references
References 44 publications
1
73
0
Order By: Relevance
“…After loading with PTX ( Figure 5(d)), Fe 3 O 4 nanoparticles were still firmly anchored on the surface of RGO. Figure 6(a), 40.4% mass loss before 200 ∘ C was due to desorption of H 2 O and pyrolysis of oxygen-containing group [24]. The pyrolysis of carbon skeleton was exhibited at 50.3% mass loss between 200 and 550 ∘ C. Figure 6(b) showed that 17.4% weight loss before 300 ∘ C was the removal of labile groups.…”
Section: Xrd Analysis As Exhibited Inmentioning
confidence: 99%
See 1 more Smart Citation
“…After loading with PTX ( Figure 5(d)), Fe 3 O 4 nanoparticles were still firmly anchored on the surface of RGO. Figure 6(a), 40.4% mass loss before 200 ∘ C was due to desorption of H 2 O and pyrolysis of oxygen-containing group [24]. The pyrolysis of carbon skeleton was exhibited at 50.3% mass loss between 200 and 550 ∘ C. Figure 6(b) showed that 17.4% weight loss before 300 ∘ C was the removal of labile groups.…”
Section: Xrd Analysis As Exhibited Inmentioning
confidence: 99%
“…Secondly, PF127 (400 mg) was dropped to Fe 3 O 4 /f-GO solution (15 mL, 1.0 mg/mL) and hydrazine monohydrate (400 L) was then added to reduce the GO [24]. After reaction, Fe 3 O 4 /RGO nanocomposites were obtained by pressure filtration.…”
Section: Synthesis Of Fementioning
confidence: 99%
“…The toxic effects of graphene can be influenced by physicochemical properties such as size and distribution, surface charge, surface area, layer number, lateral dimensions, surface chemistry, purity, particulate state, surface functional groups, and shape. 31,146,147 The mechanisms by which GO and rGO nanowalls show toxicity to E. coli and Staphylococcus aureus bacteria were demonstrated by Akhavan and Ghaderi 28 and Hu et al 148 They demonstrated that both GO and rGO are effective as antibacterial agents. Subsequently, many research laboratories have investigated the potential toxicity of GO and rGO against several bacterial species.…”
Section: Toxicity Of Graphene In Prokaryotic Cellsmentioning
confidence: 99%
“…GO was widely investigated as a nanocarrier with numerous chemotherapy drugs: doxorubicin [203,204,154,205], camptothecin [206,207], ellagic acid [208], 1,3-bis(2-chloroethyl)-1-nitrosourea [209], and b-lapachone [210]. Sun et al [193] have synthesized a conjugate of PEGylated GO with an anti-CD20 antibody, rutixan and doxorubicin.…”
Section: Delivery Of Anticancer Drugs To the Cancer Cells By Nanograpmentioning
confidence: 99%